Characteristics of Mae Moh lignite: Hardgrove grindability index and approximate work index - Chairoj Rattanakawin (2018)
The purpose of this research was to preliminarily study the Mae Moh lignite grindability tests emphasizing on Hardgrove grindability and approximate work index determination respectively. Firstly, the lignite samples were collected, prepared and analyzed for calorific value, total sulfur content, and proximate analysis. After that the Hardgrove grindability test using ball-race test mill was performed. Knowing the Hardgrove indices, the Bond work indices of some samples were estimated using the Aplan's formula. The approximate work indices were determined by running a batch dry-grinding test using a laboratory ball mill. Finally, the work indices obtained from both methods were compared. It was found that all samples could be ranked as lignite B, using the heating value as criteria, if the content of mineral matter is neglected. Similarly, all samples can be classified as lignite with the Hargrove grindability indices ranging from about 40 to 50. However, there is a significant difference in the work indices derived from Hardgrove and simplified Bond grindability tests. This may be due to difference in variability of lignite properties and the test procedures. To obtain more accurate values of the lignite work index, the time-consuming Bond procedure should be performed with a number of corrections for different milling conditions. With Hardgrove grindability indices and the work indices calculated from Aplan's formula, capacity of the roller-race pulverizer and grindability of the Mae Moh lignite should be investigated in detail further.